Knowledge gaps in legume diversity and distribution and prospects for future research - Moabe Ferreira Fernandes; Gwilym P. Lewis; Mohammad Vatanparast; Flávia Fonseca Pezzini; Matilda J. M. Brown; Luciano P. de Queiroz; Domingos Cardoso; R. Toby Pennington (Brazilian Journal of Botany, 2024)
Despite significant advancements in legume (Leguminosae or Fabaceae) taxonomy, biogeography and phylogenetics, substantial knowledge gaps persist, limiting our ability to understand their diversity, evolutionary history and conservation needs. In this study we used a robust taxonomic backbone and information housed in publicly available biodiversity repositories to quantify global knowledge gaps within the legume family, focusing on the completeness of species inventory (Linnean shortfall), geographic coverage (Wallacean shortfall), and evolutionary representation (Darwinian shortfall). Our findings underscore that approximately 11% of legume species are yet to be described, with high concentrations in regions such as Iran, Northwestern China, Western Australia, Cape Provinces, and Northeast Brazil. The assessment of gaps in geographic coverage revealed that around 19.8% of legume species lack any occurrence record in public databases. Additionally, nearly 50% of species had fewer than ten occurrence records, and another 50% had incomplete geographic coverage relative to their known distributions. Significant geographic gaps were identified in Temperate Asia, particularly Iran, Afghanistan, and Turkey. Furthermore, the limited availability of comprehensive DNA sequence data for key markers (ITS, matK , psbA , rbcL , trnL ), with 52.5% of species lacking sequences for these markers, poses challenges for accurate phylogenetic inference, especially for clades from poorly sampled regions like South America and Temperate Asia. Addressing these gaps requires integrative approaches that combine herbarium collection assessments, targeted fieldwork, enhanced data integration across repositories, and advanced phylogenetic techniques. By prioritising these strategies, we can accelerate the pace of species discovery and refine biogeographical and phylogenetic understanding for this ecologically and economically important group of plants.

A densely sampled molecular phylogeny of Tachigali (Leguminosae), an evolutionarily successful lineage of neotropical ant-housing canopy trees - Isau Huamantupa-Chuquimaco; Vitor Hugo Maia; Haroldo Cavalcante de Lima; Maristerra Rodrigues Lemes; Cristiane Snak; Bernarda Gregório; Sérgio Ricardo S. Cardoso; Luciano Paganucci de Queiroz; Charles E. Zartman; Gwilym P. Lewis; Euan K. James; Kyle G. Dexter; et al. (Brazilian Journal of Botany, 2024)

Estimating stocking weights for Atlantic salmon to grow to market size at novel aquaculture sites with extreme temperatures - Danielle P. Dempsey; Gregor K. Reid; Leah Lewis-McCrea; Toby Balch; Roland Cusack; André Dumas; Jack Rensel (Frontiers in Marine Science, 2023)
Land-based hatcheries are now capable of growing large Atlantic salmon ( Salmo salar ) post-smolts (approximately 150 – 1000 g), which means that marine net-pens can be stocked with substantially larger fish compared to traditional stocking sizes (< 150 g). This stocking strategy typically aims to reduce the time required for fish to grow to market size in the marine environment and limit risks (e.g., exposure to pathogens and diseases, opportunities for escapes). This study investigates another potential application of this strategy: the use of novel sites in areas previously considered unsuitable for aquaculture due to seasonally cold temperatures. The thermal-unit growth coefficient (TGC) model was applied to estimate the stocking weight needed to reach a harvest size of 5.5 kg, based on observed degree days for three sites. High resolution, depth-partitioned temperature time series from coastal locations in Atlantic Canada were used to represent a short, medium, and long growing season, as constrained by seasonal temperature extremes. Growing days for model inputs were defined as temperatures > 4 °C and trending up for stocking, < 18 °C to account for heat stress, and > -0.7 °C to avoid superchill conditions. Different TGC values were applied to simulate remedial, average, and elite growth performance. There was a range of model stocking weight estimates for each site (1.5 – 2.5 kg, 0.94 – 2.8 kg, and < 0.1 – 0.52 kg, for the short, medium, and long season sites, respectively). Results were sensitive to the number of degree days, heat stress threshold, and TGC value. At the two sites where season length was constrained by superchill, fish with a stocking weight of approximately 1.5 kg could grow to market size in shallow water depths (< 15 m), assuming elite growth performance. This investigation suggests that with appropriate growth performance assumptions and high-resolution temperature data, large post-smolt stocking strategies could enable the use of novel sites in coastal areas previously considered unsuitable for aquaculture.

Resource quality determines the evolution of resistance and its genetic basis - Katherine E. Roberts; Sean Meaden; Stephen Sharpe; Suzanne Kay; Toby Doyle; Drew Wilson; Lewis J. Bartlett; Steve Paterson; Mike Boots (Molecular Ecology, 2020)
Parasites impose strong selection on their hosts, but the level of any evolved resistance may be constrained by the availability of resources. However, studies identifying the genomic basis of such resource‐mediated selection are rare, particularly in nonmodel organisms. Here, we investigated the role of nutrition in the evolution of resistance to a DNA virus (PiGV), and any associated trade‐offs in a lepidopteran pest species ( Plodia interpunctella ). Through selection experiments and whole‐genome resequencing, we identify genetic markers of resistance that vary between the nutritional environments during selection. We do not find consistent evolution of resistance in the presence of virus but rather see substantial variation among replicate populations. Resistance in a low‐nutrition environment is negatively correlated with growth rate, consistent with an established trade‐off between immunity and development, but this relationship is highly context dependent. Whole‐genome resequencing of the host shows that resistance mechanisms are likely to be highly polygenic and although the underlying genetic architecture may differ between high and low‐nutrition environments, similar mechanisms are commonly used. As a whole, our results emphasize the importance of the resource environment on influencing the evolution of resistance.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Fast demographic traits promote high diversification rates of Amazonian trees - Timothy R. Baker; R. Toby Pennington; Susana Magallon; Emanuel Gloor; William F. Laurance; Miguel Alexiades; Esteban Alvarez; Alejandro Araujo; Eric J. M. M. Arets; Gerardo Aymard; Atila Alves de Oliveira; Iêda Amaral; et al. (Ecology Letters, 2014)
The Amazon rain forest sustains the world's highest tree diversity, but it remains unclear why some clades of trees are hyperdiverse, whereas others are not. Using dated phylogenies, estimates of current species richness and trait and demographic data from a large network of forest plots, we show that fast demographic traits – short turnover times – are associated with high diversification rates across 51 clades of canopy trees. This relationship is robust to assuming that diversification rates are either constant or decline over time, and occurs in a wide range of Neotropical tree lineages. This finding reveals the crucial role of intrinsic, ecological variation among clades for understanding the origin of the remarkable diversity of Amazonian trees and forests.

Use of free-standing filters in an asthma intervention study - Stuart Batterman; Liuliu Du; Edith Parker; Thomas Robins; Toby Lewis; Bhramar Mukherjee; Erminia Ramirez; Zachary Rowe; Wilma Brakefield-Caldwell (Air Quality, Atmosphere & Health, 2013)